COMMITMENT Of One Of The DOCTRINES SHAYKH AHMED IBN Al-SAYYID MUHAMMAD IBN Al-S SAYYID YASSIN SON Of SHEIKH ABDUL GHANI Al - HUSSEINI Al - SHAFIE(1224 H) - Ali, Bilal (Islamic Sciences Journal, 2023)
This is a short message in the fundamentals of jurisprudence on the doctrine of Imam Shafi'i (may Allah have mercy on him) to Sheikh Ahmad Ibn al-Sayyid Muhammad Ibn al-Sayyid Yassin al-Habrawi, nicknamed the second Shafi'i, from the people of Aleppo Al-Shahba, the work of God's mercy in this letter of the important doors in the fundamentals of jurisprudence; And the second is the general obligation of a specific religion. It is not secret to the scholars of the importance of these two issues in the chapter of fatwa. This is the intention of the matter, relying on Allah Almighty To achieve this message, as for the board of the manuscript has dominated the work P (may God have mercy on him) highlights the tradition of the general to strive in the matter of what is his reference to the other Mufti? , And the disagreement in that detailed, and then the second question and the views of scientists in the commitment of a certain doctrine between the transferees and the abstainers and the conditions of this detailed, in addition to the issue of (tracking licenses). In conclusion we ask conciliation and repayment, God arrived on our master Muhammad and his family and companions.